EXTRACTION AND CHARACTERIZATION OF CHITIN AND CHITOSAN FROM LOCAL IRAQI FISH SCALES - Shemaa A. Soud; Maysaa A. Ali; Wedean G. Alhadban; Ali A. Taha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Both chitin and deacylated form of chitosan are considered the second most biopolymer available in nature after cellulose. Chitin and chitosan have an economic value related to their industrial, biological and biomedical applications. In this study, chitin was extracted from of Iraqi carp fish scales (Cyprinus carpio L.) and then deacylated into the chitosan. The obtained samples have been distinguished through Fourier transforms infrared spectroscopy (FTIR) and Thermo gravimetric analysis (TGA). The FTIR analysis for chitin showed the characteristic spectra at 1541 cm-1 and 1647 cm-1 associated to N-H bending vibration and C=O stretching vibration respectively. Thus, the FTIR spectra of chitosan gave characteristics bands of 1647 cm-1 for a carbonyl group. Thus, thermogravimetric analysis suggests that chitin had been found to be more stable than chitosan. Moreover, study of physiochemical properties for obtained chitosan was identified the molar mass (MW) of prepared chitosan to be 2.5 x 105(g/mol) with 4.5%moisture content, 0.050% ash and insoluble content about 0.59%. The degree of deacetylation (DD) was also studied based on potentiometric titration and FTIR were reached to 57% and 63% respectively. It has been confirmed by the functional properties of the prepared chitosan that it can be commercially used in different fields. Preparing chitosan from fish waste would be minimise the pollutants to the environment.